Effect Of Additive Al On the Optical Properties Of Polystyrene-Aluminum Composites - Abdul Zahra, Sawsan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Additive aluminum powder to the polystyrene to prepare the composites Polystyrene– Aluminum.The samples were prepared by using mechanical compressed method at low pressure and a temperature 120°C. Measurements of absorbance and reflectance spectra were carried out by UV-Visible spectrophotometer , the effect of additive aluminum on the optical band gap Eop and optical constants ( refractive index n, extinction coefficient k ,dielectric constant ε and optical conductivity σop) were studied for the prepared composites . Results showed a decrease in the Eop with increasing percent of aluminum from 4.1eV for pure polystyrene to about 3.12eV for the composite Ps+30%Al. Values of each of n and k show observable changes, these changes are associated with the increase in scattering, reflection, and optical absorption on the film surface with the increase of Al percentage. The dielectric constant of Ps-Al composites is greater for all Al concentrations and may be attributed to interfacial polarization in the heterogeneous media, it was observed that the optical conductivity increasing from 0.12×105S.cm-1 for pure polystyrene to about 1.32×108S.cm-1 for Ps+30%Al. These results indicate that the optical properties of PS-Al composites can be controlled by the appropriate selection of Al concentration and the optical properties of the composites can be modified by the addition of impurities ,thus increase the industrial application for the composites.